2019
DOI: 10.30574/gscbps.2019.8.3.0152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium azide on agro-morphological traits of four varieties of Kenaf (Hibiscus cannabinus)

Abstract: Mutation induction and detection of desired mutants represents an accelerated means of reaching the desired superior Variety. In this work seeds of Kenaf varieties NG, HIB18, HIB24 and HIB42 collected from National Centre for Genetic Resources and Biotechnology (NAGRAB) Ibadan, Nigeria were subjected to mutagenesis using sodium azide at concentrations of 0.2%, 0.4%, and 0.6%. These treated seeds were planted in polythene bags in row of Four by Four columns in a completely Randomized Design (CRD) with three rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The drastic reduction in the germination with increase in the concentration of sodium azide may be due to the induction of chromosomal structure abnormalities in the genes of vitality. This result is in synchronization with Abu et al (2020) and Ibukun et al (2019).…”
Section: Germination Percentsupporting
confidence: 70%
See 1 more Smart Citation
“…The drastic reduction in the germination with increase in the concentration of sodium azide may be due to the induction of chromosomal structure abnormalities in the genes of vitality. This result is in synchronization with Abu et al (2020) and Ibukun et al (2019).…”
Section: Germination Percentsupporting
confidence: 70%
“…In the both variety MP 3382 and RVW 4106, SA significantly reduced but HA significantly increased the germination percentage and root length as compared to control as shown in Table 6. Ibukun et al (2019) have also reported these results. The mutagen HA acted in a reverse trend with that of HA.…”
Section: Germination Percentage and Root Lengthmentioning
confidence: 53%